Active skills for reading 2 - Anderson, Neil J. (Boston, Mass. : National Geographic Learning ; Heinle Cengage Learning, 2013)
A guides that develops learners' reading comprehension and vocabulary skills. It uses an Active approach to help learners become confident, independent - and active-readers.
Unit 1: Exam TimeUnit 2: Going AbroadUnit 3: Move MakersUnit 4: Young AthletesUnit 5: The Amazing Human BodyUnit 6: Leisure TimeUnit 7: A World of MusicUnit 8: Career PathsUnit 9: The Story of ChocolateUnit 10: The Secrets of AdvertisingUnit 11: Food and the EnvironmentUnit 12: Living for the Future
language bookfair2015
Keywords: English language -- Study and teaching -- Foreign speakers; Reading comprehension -- Problems, exercises, etc; Vocabulary -- Problems, exercises, etc